ICD-10 Coding of Musculoskeletal Conditions in the Veterans Health Administration. Issue 11 (4th May 2021) - Coleman, Brian C; Goulet, Joseph L; Higgins, Diana M; Bathulapalli, Harini; Kawecki, Todd; Ruser, Christopher B; Bastian, Lori A; Martino, Steve; Piette, John D; Edmond, Sara N; Heapy, Alicia A
Abstract: Objective: We describe the most frequently used musculoskeletal diagnoses in Veterans Health Administration care. We report the number of visits and patients associated with common musculoskeletal International Classification of Diseases (ICD)-10 codes and compare trends across primary and specialty care settings. Design: Secondary analysis of a longitudinal cohort study. Subjects: Veterans included in the Musculoskeletal Diagnosis Cohort with a musculoskeletal diagnosis from October 1, 2015, through September 30, 2017. Methods: We obtained counts and proportions of all musculoskeletal diagnosis codes used and the number of unique patients with each musculoskeletal diagnosis. Diagnosis use was compared between primary and specialty care settings. Results: Of more than 6, 400 possible ICD-10 M-codes describing "Diseases of the Musculoskeletal System and Connective Tissue, " 5, 723 codes were used at least once. The most frequently used ICD-10 M-code was "Low Back Pain" (18.3%), followed by "Cervicalgia" (3.6%). Collectively, the 100 most frequently used codes accounted for 80% of M-coded visit diagnoses, and 95% of patients had at least one of these diagnoses. The most common diagnoses (spinal pain, joint pain, osteoarthritis) were used similarly in primary and specialty care settings. Conclusion: A diverse sample of all available musculoskeletal diagnosis codes were used; however, less than 2% of all possible codes accounted for 80% of the diagnoses used. This trend was consistent across primary and specialty care settings. The most frequently used diagnosis codes describe the types of musculoskeletal conditions, among a large pool of potential diagnoses, that prompt veterans to present to the Veterans Health Administration for musculoskeletal care.